2017
DOI: 10.1186/s40461-017-0047-2
|View full text |Cite
|
Sign up to set email alerts
|

Commercial competence: comparing test results of paper-and-pencil versus computer-based assessments

Abstract: Background: Vocational education and training (VET) aims to enable young adults or trainees to participate in the workplace, and to promote their vocational capacities. In order to examine trainees' competencies at the end of VET, appropriate instruments are needed. This contribution aims: (1) to give an outline of such an instrument, one that has been designed to evaluate vocational competencies in the field of economics, and (2) to present the results of an empirical comparison of two possible test modes: co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…As such, school administration should play a facilitating role in giving the teachers a helping hand, in this case, the excellent teachers, to lessen their burden caused by overwhelming documentation. Interestingly, scholars also suggested that digitisation of the assessment of the task could be carried out in the 21st-century as it will allow for the learners to be tested more vigorously using the state-of-the-art methods [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…As such, school administration should play a facilitating role in giving the teachers a helping hand, in this case, the excellent teachers, to lessen their burden caused by overwhelming documentation. Interestingly, scholars also suggested that digitisation of the assessment of the task could be carried out in the 21st-century as it will allow for the learners to be tested more vigorously using the state-of-the-art methods [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…[15]. This technique is used to find out whether certain scores are significantly different or not with the median of a sample [14]. The output of tone sample test on learning interest shows that the class used as experiment scored a mean of 57.00, which means there is a difference in learning interests by using a better module categorized as Advanced.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the t test counting result of one sample test SPSS program that aims to differentiate [14], this technique is used to test the output counting of test of normality [10], which shows the significance score result of control class for 0.200 and significance score of experimental class for 0.118. Therefore, the second result is considered normal.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in universities, remote learning and assessment through free software web conferencing systems such as BigBlueButton is being used, and the exams are usually conducted through computer, because some features of software may not be shown in mobile. Score interchangeability between CFLT and PPBT as the controversial issue in the last decade (Sangmeister, 2017) in Computer-Based Testing field should be investigated empirically through studying psychometric properties (Burr et al, 2016) as the prerequisite of replacing CFLT with PPBT (Khoshsima et al, 2019;Rausch, Seifried, Wuttke, Kogler and Brandt, 2016). Therefore, since authenticating and sustaining validity and reliability of measurement is essential for replacing CFLT with PPBT, the current study concentrated on whether validity and reliability measurement would be violated by changing testing administration mode and whether scores received from PPBT and CFLT would be interchangeable or equivalent (TEA, 2008).…”
Section: Introductionmentioning
confidence: 99%